African Union and Libyan Crises, 2011-2022 - Hart, Akie Opuene, PhD; ANYALEBECHI, Shammah Mahakwe, PhD; Amabibi, Ferdinand, PhD; Eyina, Nkatomba, PhD (Genius Journals, 2023)
The African Union (AU) is facing significant challenges in its efforts to resolving the Libyan crisis. The civil war that erupted in Libya in 2011 has displaced millions of people and caused severe human suffering, destruction of infrastructure, and instability in the region. Despite various diplomatic initiatives, the conflict has reached a stalemate. While the AU has been a major player in the search for a solution, it has had limited success in this regard. To this end, the study examined the roles of the AU in Libya's crises. This study was anchored on the constructivism theory propounded by Alexander Wendt in 1992, while a historical and qualitative approach were employed for the study. The secondary source of data collection was used in this investigation, and data was obtained by surfing from published works and research on AU publications on peaceful resolution of Libyan crises, textbooks, journals, magazines, newspapers, government publications, and other allied materials. The secondary data collected relating to AU efforts in finding a peaceful resolution to the Libyan crises was thoroughly subjected to content analysis. The study revealed that economic hardships, the spread of anti-government sentiment, and the international intervention of NATO forces contributed to the Libyan crisis of 2011. Also, the US CIA’s role in the Libyan crisis has been significant and varied, ranging from providing logistical and material support to training militia forces and gathering intelligence, resulting in the overthrow of the Gaddafi regime and the formation of a new government. The African Union's initiatives towards the Libyan crisis have been hindered by the lack of a unified stance taken by its member states towards the conflict. From the identified findings, the study recommended that there is a need for the African Union to facilitate more direct dialogue among its member states to reach a unified stance based on mutual interests. This is important because it would provide the basis for the AU to take action in the crisis; without a unified stance, the AU will be unable to effectively intervene and resolve the conflicts.
Keywords: Africa Union; Crisis; Uprising; Peace